Adenovirus type 2 preferentially stimulates polymerase III transcription of Alu elements by relieving repression: a potential role for chromatin. - Russanova, V R (1995)
The number of Alu transcripts that accumulate in HeLa and other human cells is normally very low; however, infection with adenovirus type 5 increases the expression of Alu elements dramatically, indicating that the potential for polymerase III (pol III)-dependent Alu transcription in vivo is far greater than generally observed (B. Panning and J.R. Smiley, Mol. Cell. Biol. 13:3231-3244, 1993). In this study, we employed nuclear run-on in combination with a novel RNase H-based assay to investigate transcription from uninfected and adenovirus type 2-infected nuclei, as well as genomic DNAs from uninfected and infected cells. When performed in the presence of excess uninfected nuclear extract, such assays revealed that (i) the vast majority of transcriptionally competent Alu elements in nuclei are masked from the pol III transcriptional machinery and (ii) the induction of Alu expression upon adenovirus infection can be largely accounted for by an increased availability of these elements to the pol III transcription machinery. We also investigated the role of H1 histone for silencing of Alu genes and, in comparison, mouse B2 repetitive elements. Depletion of H1 led to an approximately 17-fold activation of B2 repetitive elements but did not change Alu transcription relative to that of constitutively expressed 5S rRNA genes. These results are consistent with the view that Alu repeats are efficiently sequestered by chromatin proteins, that such masking cannot be accounted for by nonspecific H1-dependent repression, and that adenovirus infection at least partially overrides the repressive mechanism(s).